Neutrophils: tissue and circulating signatures of pediatric non-alcoholic fatty liver disease - Săsăran, Maria Oana; Muntean, Carmen; Lupu, Ancuța; Lupu, Vasile Valeriu (Frontiers in Cell and Developmental Biology, 2024)
The recent rise in non-alcoholic fatty liver disease (NAFLD) among children and adolescents led to a thorough investigation of the peculiarities of the cellular infiltrate which characterize the disease at young ages. This review aims to highlight the key involvement of neutrophils in the pathogenesis of pediatric NAFLD and the potential biomarker role of neutrophil-to-lymphocyte ratio (NLR) in the same pediatric disorder. Neutrophils, which are first responders to inflammation, constitute an abundant component of an infiltrate which is particularly disposed within the portal area of children with NAFLD. The involvement of neutrophils in triggering liver fibrosis has been related amongst others to reactive oxygen species (ROS) production, to the stimulation of hepatic stellate cells, and to their synthesis of neutrophil elastase. As immune imbalance characterizes NAFLD, potentially emerging non-invasive biomarkers such as NLR have been proposed for the detection and prognosis of NAFLD. In adults, several studies asserted the role of NLR in the prediction of advancing liver fibrosis and mortality in subjects with NAFLD. In children, data is scarce with contradicting findings, as some studies failed to identify significant shifting in NLR values in children with NAFLD, when compared with obese controls without liver impairment. However, NLR seems to significantly increase in children with obesity and different degrees of NAFLD when compared to healthy counterparts and their changes seem to be reversible with weight loss. Still, paucity of pediatric studies calls for future research addressing the role of NLR in predicting NAFLD development and progression in children with obesity.